A Novel, W-Band Microwave Based Contactless Test Method for Mechanical Sensitivity Analysis of MEMS - Oesterle, Florian; Vinci, Gabor; Weigel, Robert; Kölpin, Alexander (IEEE International Microwave Symposium, 2013)
The desired functionality of Micro Electro Mechanical Systems (MEMS) suffers from the influence on the nominal stress level of the mechanical components, e.g. by deviating manufacturing process parameters. Therefore, appropriate methods for testing mechanical parameters of MEMS is a key issue. The focus is on contactless techniques, short measurement time, accurate repeatability, and inline integration in manufacturing environments for mass production. Depending on the configuration of the device components, a couple of methods, such as optical interferometry, electrical impedance measurements and system level sensitivity tests are nowadays in use. This article presents a novel method for contactless testing of mechanical sensitivity of MEMS devices based on W-band microwave interferometry. Results of measurements at 90GHz are shown. The excellent detection of the test parameter verifies the feasibility and enormous potential of this proposed method.
elib2cris::1512001600,oesterle2013
Keywords: Microelectromechanical Systems; Contactless Testing; Microphones; Mechanical Sensitivity; Microwave Interferometry; W-band